2010
DOI: 10.4067/s0717-65382010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidad genética local del bivalvo dulceacuícola Diplodon chilensis (Gray 1828) proveniente de tres lagos Nahuelbutanos

Abstract: Genetic variability of a freshwater bivalve Diplodon chilensis from three Nahuelbuta lakes was described. Each lake shows geographic barriers and environmental characteristics as a consequence of geomorphologic and antropic events. Our results shows that only Lleu-Lleu lake was in Hardy-Weinberg equilibrium (P<0.05). All populations show gametic desequilibrium (P < 0.001), as an evidence of the species' life cycle. There are heterozygote deficiencies (Fis) in Laguna La Posada and Laguna Chica de San Pedro. Glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(57 reference statements)
1
2
0
2
Order By: Relevance
“…Figure 1 an indication of the stability of the species, that is, that the population of Octopus maya is demographically stable, indicating that this population has not been subject to recent genetic events, as it may have been subject to a founding effect or recurrent bottlenecks; in fact, one of the aspects that makes this species desirable to be exploited is its high population size. Considering the care that must be taken when comparing allozimic data, the heterozygosis values detected in this study are relatively higher than those detected by the determination of isoenzymes in other cephalopod species, but still within the established range for invertebrate organisms, where a generalized occurrence of heterozygosis deficiency relative to Hardy-Weinberg law expectations has been fully reported in studies of isoenzymes in marine mollusks and other invertebrates (Maltagliati et al, 2002a, Maltagliati et al, 2002bDoubleday 2009;Quiang et al, 2009;Fuentealba et al, 2010;Hmida et al, 2012). The average heterozygosis values for the populations in O. maya are between 0.1142 and 0.1390 (Table 1) and the outputs of the Hardy-Weinberg equilibrium law are mainly supported by some loci such as EST1 and G6PDH1 (data not shown) in most populations.…”
Section: Resultssupporting
confidence: 54%
“…Figure 1 an indication of the stability of the species, that is, that the population of Octopus maya is demographically stable, indicating that this population has not been subject to recent genetic events, as it may have been subject to a founding effect or recurrent bottlenecks; in fact, one of the aspects that makes this species desirable to be exploited is its high population size. Considering the care that must be taken when comparing allozimic data, the heterozygosis values detected in this study are relatively higher than those detected by the determination of isoenzymes in other cephalopod species, but still within the established range for invertebrate organisms, where a generalized occurrence of heterozygosis deficiency relative to Hardy-Weinberg law expectations has been fully reported in studies of isoenzymes in marine mollusks and other invertebrates (Maltagliati et al, 2002a, Maltagliati et al, 2002bDoubleday 2009;Quiang et al, 2009;Fuentealba et al, 2010;Hmida et al, 2012). The average heterozygosis values for the populations in O. maya are between 0.1142 and 0.1390 (Table 1) and the outputs of the Hardy-Weinberg equilibrium law are mainly supported by some loci such as EST1 and G6PDH1 (data not shown) in most populations.…”
Section: Resultssupporting
confidence: 54%
“…It has been postulated that variations in certain life history traits between D. chilensis populations from lotic and lentic environments could be due to genetic differences [49], although a karyological study contradicted this hypothesis [50]. Consistent with the latter, it has been reported that the populations of this clam from different basins near the Pacific coast in southern Chile are not genetically structured [51], and that differences found in the growth rates can be associated with geographic and limnological parameters [32].…”
Section: Discussionmentioning
confidence: 90%
“…Lakes with a surface area ≥ 10 km 2 were selected based on [6]. The 14 selected lakes present a temperate monomictic circulation pattern, with thermal stratification during summer [34][35][36][37]. At present, 11 of the lakes chosen in this study are oligotrophic, while Villarrica has been classified as meso-oligotrophic, and Vichuquén and Lanalhue, as eutrophic [38].…”
Section: Introductionmentioning
confidence: 99%